Chromosomal aberrations and early mortality in a non-mammalian vertebrate: example from pressure-induced triploid Atlantic salmon ... - Delaval, Aurélien; Glover, Kevin A.; Solberg, Monica F.; Fjelldal, Per Gunnar; Hansen, Tom; Harvey, Alison C. (Dryad, 2025)
In commercial aquaculture, the production of triploid fish is currently the most practical approach to prevent maturation and farm-to-wild introgression following escapes. However, triploids often exhibit poor welfare, and the underlying mechanisms remain unclear. Inheritance issues associated with sub-optimal hydrostatic pressure treatments used to induce triploidy, or the genetic background of parental fish, have been speculated to contribute. We tested this by quantifying the frequency and type of chromosomal aberrations in Atlantic salmon subjected to a gradient of sub-optimal pressure treatments (Experiment 1) and from multiple mothers (Experiment 2). From these experiments, we genotyped a subsample of ~900 eyed eggs and all ~3,300 surviving parr across ~20 microsatellites. In contrast to the low frequency of chromosomal aberrations in the diploid (no hydrostatic pressure) and triploid (full 9,500 PSI treatment) controls, eyed eggs subjected to sub-optimal pressure treatments (6,500 – 8,500 PSI) had a ... : # Chromosomal aberrations and early mortality in a non-mammalian vertebrate: example from pressure-induced triploid Atlantic salmon Three datasets are provided as a supplement to the associated article. Each dataset contains data from two experiments. In the first experiment, Atlantic salmon offspring from three half-sibling families (3 dams, 1 common sire) were subjected to five hydrostatic pressure treatments shortly after fertilization. This was to explore the effects of sub-optimal pressure treatments (6500 PSI, 7500 PSI, and 8500 PSI) on ploidy and inheritance, compared to standard diploid (0 PSI) and triploid (9500 PSI) controls. In the second experiment, Atlantic salmon offspring from twelve half-sibling families (12 dams, 1 common sire) were subjected to two hydrostatic pressure treatments representing standard diploid and triploid procedures (0 PSI and 9500 PSI). This was to further explore family effects on ploidy and inheritance following standard diploid (0 PSI) and triploid (9500 PSI) ...